How do you multiply (- 2) ^ { - 2} \cdot ( - 2) ^ { - 3} \cdot ( - 2) ^ { 4}?

2 Answers

= -1/2

Explanation:

Since you're multiplying three terms with the same base of -2, you can simply add up the exponents.

(-2)^-2*(-2)^-3*(-2)^4
= (-2)^-1

Since this is a negative exponent you need to take the reciprocal of -2. The denominator will have a positive exponent, but the same base.

1/(-2)^1
= -1/2

Jan 24, 2018

-1/(2)

Explanation:

When multiplying powers where the base is the same, add the exponents:

Your equation would be equal to =(-2)^((-2)+(-3)+4)

This gives (-2)^(-1)

Since the exponent is negative 1, it means the reciprocal of the base:

(-2)^(-1)=-1/(2)